A High-Resolution Earth’s Gravity Field Model SGG-UGM-2 from GOCE, GRACE, Satellite Altimetry, and EGM2008 - Wei Liang; Jiancheng Li; Xinyu Xu; Shengjun Zhang; Yongqi Zhao (Engineering, 2020)
This paper focuses on estimating a new high-resolution Earth’s gravity field model named SGG-UGM-2 from satellite gravimetry, satellite altimetry, and Earth Gravitational Model 2008 (EGM2008)-derived gravity data based on the theory of the ellipsoidal harmonic analysis and coefficient transformation (EHA-CT). We first derive the related formulas of the EHA-CT method, which is used for computing the spherical harmonic coefficients from grid area-mean and point gravity anomalies on the ellipsoid. The derived formulas are successfully evaluated based on numerical experiments. Then, based on the derived least-squares formulas of the EHA-CT method, we develop the new model SGG-UGM-2 up to degree 2190 and order 2159 by combining the observations of the Gravity Field and Steady-State Ocean Circulation Explorer (GOCE), the normal equation of the Gravity Recovery and Climate Experiment (GRACE), marine gravity data derived from satellite altimetry data, and EGM2008-derived continental gravity data. The coefficients of degrees 251–2159 are estimated by solving the block-diagonal form normal equations of surface gravity anomalies (including the marine gravity data). The coefficients of degrees 2–250 are determined by combining the normal equations of satellite observations and surface gravity anomalies. The variance component estimation technique is used to estimate the relative weights of different observations. Finally, global positioning system (GPS)/leveling data in the mainland of China and the United States are used to validate SGG-UGM-2 together with other models, such as European improved gravity model of the earth by new techniques (EIGEN)-6C4, GECO, EGM2008, and SGG-UGM-1 (the predecessor of SGG-UGM-2). Compared to other models, the model SGG-UGM-2 shows a promising performance in the GPS/leveling validation. All GOCE-related models have similar performances both in the mainland of China and the United States, and better performances than that of EGM2008 in the mainland of China. Due to the contribution of GRACE data and the new marine gravity anomalies, SGG-UGM-2 is slightly better than SGG-UGM-1 both in the mainland of China and the United States.